The military and denied development in the Pakistani Punjab : an eroding social consensus - Khan, Shahrukh Rafi; Akhtar, Aasim Sajjad; Bodla, Sohaib (London : Anthem Press, 2014)
This book focuses on the retrogressive agrarian interventions by the Pakistani military in rural Punjab and explores the social resentment and resistance it triggered, potentially undermining the consensus on a security state in Pakistan. Set against the overbearing and socially unjust role of the military in Pakistan's economy, this book documents a breakdown in the accepted function of the military beyond its constitutionally mandated role of defence. Accompanying earlier work on military involvement in industry, commerce, finance and real estate, the authors' research contributes to a wider understanding of military intervention, revealing its hand in various sectors of the economy and, consequently, its gains in power and economic autonomy.
The military and economic development in Pakistan -- Punjab's state-society consensus on the military's dominance and economic role -- Research design, method, institutional issues, and scope of the military's land acquisitions -- The military's land acquisitions: high handedness and social resentment -- From social resentment to social resistance -- Bahria Town: a military-related real estate venture -- The military as landlord in Pakistani Punjab: a case study of the Okara farms -- Guardians no more? The breakdown of the consensus.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Civil-military relations -- Pakistan -- Punjab; Armed Forces -- Economic aspects -- Pakistan -- Punjab; Economic development -- Pakistan -- Punjab; Armed Forces -- Social aspects -- Pakistan -- Punjab; Military-owned business enterprises -- Pakistan -- Punjab; Military government -- Economic aspects -- Pakistan -- Punjab; Land tenure -- Pakistan -- Punjab